Evaluation of Dry Lab Training on Residents Knowledge of Robotic Instrumentation and Surgical Preparation. (October 2016) - Rohl, Jacqueline; Hade, Erinn
Abstract : BACKGROUND: Current studies of robotic surgery training are focused primarily on education and evaluation of surgical skills acquisition. However, a component not well studied is knowledge of instrumentation and surgical preparation (port placement, docking, and console knowledge). METHODS: Evaluation of residents knowledge was completed by a short pre and post-test consisting of 16 questions on patient positioning (maximum of 2 points), docking/patient cart information (maximum of 16 points) and the surgeon console (maximum of 12 points). The total score is calculated as the sum of these three components (range: 0–30). Residents demographics, pre-test, post-test and recall test total scores are summarized by descriptive statistics. The comparison of scores before and after training is made by the Wilcoxon signed-rank test and through regression on the ranks of the scores. Rank regression models allow adjustment of residents demographics characteristics on the change in scores. RESULTS: Twenty-seven residents participated in the dry lab training session. There was a significant increase in test scores after the dry lab in comparison to test scores before (pre-test score: median=24, range (7–28) versus post-test score: median=29, range (22–30); Wilcoxon rank sum test P =.002). DISCUSSION: Test scores after the dry lab significantly increased in comparison to before the lab. However, tests at 3–4 months were lower than tests after the lab, especially for more junior residents. This indicates that although there was knowledge attained from the dry lab, it may need more reinforcement throughout the year.